2009
DOI: 10.5194/hess-13-1685-2009
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of moisture in Europe: contribution of evaporation to variability in very wet and dry years

Abstract: Abstract. Evaporation is a key parameter in the regional atmospheric water cycle. Precipitation recycling is defined as the contribution of water that evaporates from a region to precipitation within the same region. We apply a dynamic precipitation recycling model, which includes a dynamic moisture storage term, to calculate the warm season variability of the precipitation recycling over central Europe at a daily time scale for 2003 (dry) and 2006 (wet).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…However, the eastward extension is probably due to the heat low response over Central Europe, blocking the inflow of moist maritime air from the Atlantic and reinforcing the northward extension dynamically, as addressed by Haarsma et al (2008). Using a moisture tracer model, Bisselink and Dolman (2009) also found that advection is the most important contributor to precipitation over central Europe.…”
Section: Discussionmentioning
confidence: 93%
“…However, the eastward extension is probably due to the heat low response over Central Europe, blocking the inflow of moist maritime air from the Atlantic and reinforcing the northward extension dynamically, as addressed by Haarsma et al (2008). Using a moisture tracer model, Bisselink and Dolman (2009) also found that advection is the most important contributor to precipitation over central Europe.…”
Section: Discussionmentioning
confidence: 93%
“…Terrestrial moisture produced by evaporation has been recognized as an important component of the local precipitation (Savenije, 1995;Trenberth, 1999;Trenberth et al, 2003;Bisselink and Dolman, 2009;Seneviratne et al, 2010), especially in the vicinity of large lake systems, where water evaporates from the surface and exerts a direct influence on the climate of surrounding areas (Scott & Huff, 1996, Schaetzl, 2002, Henne et al, 2007. Using an isotopic technique, Gat and Matsui (1991) calculated that evaporation from the surface of fresh water bodies provided approximately 20-40% of local atmospheric vapor in the Amazon basin.…”
Section: Introductionmentioning
confidence: 99%
“…Seneviratne et al, 2010, for a review), the question arises if its memory may propagate to other quantities that are at least partly driven by soil moisture. For example, runoff and evapotranspiration may be highly dependent on soil moisture under certain conditions (Eagleson, 1978;Koster and Milly, 1997;Koster et al, 2004;Botter et al, 2007;Bisselink and Dolman, 2009;Kirchner, 2009;Teuling et al, 2009), therefore soil moisture memory may induce persistence in these quantities.…”
Section: Introductionmentioning
confidence: 99%